An Examination of Comment Letters Filed in the U.S. Financial Accounting Standard-Setting Process by Institutional Interest Groups. - Saemann, Georgia (Abacus)
Documents the nature of comments filed by the Financial Executives Institute, Institute of Management Accountants, Association for Investment Management and Research and the American Institute of Certified Public Accountants in the US Financial Accounting Standards Board's standard-setting process. Financial statement preparers; Financial statement users.